2021
DOI: 10.1111/cen.14549
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of 756 patients with differentiated thyroid cancer and excellent response to treatment: An evidence‐based paradigm for long‐term surveillance strategies

Abstract: Background The 2014 British Thyroid Association thyroid cancer guidelines recommend lifelong follow‐up of all thyroid cancer patients. This is probably unnecessary, particularly for differentiated thyroid cancer (DTC) patients with an excellent response to treatment and places significant demand on health service resources. Design Single centre retrospective cohort analysis of patients diagnosed and treated at the Leeds Cancer Centre between 2001 and 2014. Patients A total of 756 patients were dynamically risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…To date, only a few studies have assessed the prognostic role of the ATA risk criteria integrated with the response to initial therapy [ 28 , 29 , 30 ]. Seejore et al evaluated a large cohort of 756 DTC patients who achieved an excellent response to treatment at the first evaluation after initial therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, only a few studies have assessed the prognostic role of the ATA risk criteria integrated with the response to initial therapy [ 28 , 29 , 30 ]. Seejore et al evaluated a large cohort of 756 DTC patients who achieved an excellent response to treatment at the first evaluation after initial therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Only 15 patients (2.0%) developed radiological disease recurrence after a median follow-up of 11.2 years. They further analyzed the outcomes according to postoperative ATA risk stratification and showed that patients with an excellent response after initial therapy and classified as having a high-risk disease according to the ATA guidelines had an almost threefold higher recurrence rate (2/34 (5.9%) vs. 13/722 (1.8%)) than those with ATA low- or intermediate-risk disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Ito et al [28] found that patients with BRAFV600E were equally distributed amongst both high-and low-risk cases. So far, no single marker can predict clinical outcome or structural recurrence [29], and thorough disease surveillance is required for BIR patients [25,30].…”
Section: Developing Structural Recurrencementioning
confidence: 99%
“…The American Thyroid Association (ATA) guidelines (version 2015) state that 131 I ablation should be performed selectively for DTC patients according to different recurrence risk stratifications and is not necessary for all patients. Patients with intermediate-risk DTC should be monitored more closely in terms of therapeutic effects because of the higher probability of disease persistence and recurrence after the initial 131 I ablation [9][10][11]. Until recently, there were still controversies about whether patients with intermediate-risk DTC could benefit from initial 131 I ablation and if 131 I ablation should even be used as a routine clinical treatment due to the lack of authoritative and systematic evidence-based recommendations.…”
Section: Introductionmentioning
confidence: 99%